Furaquinocins K and L: Novel Naphthoquinone-Based Meroterpenoids from Streptomyces sp. Je 1-369 - Stepan Tistechok; Marc Stierhof; Maksym Myronovskyi; Josef Zapp; Oleksandr Gromyko; Andriy Luzhetskyy (MDPI AG, 2022)
Actinomycetes are the most prominent group of microorganisms that produce biologically active compounds. Among them, special attention is focused on bacteria in the genus Streptomyces. Streptomycetes are an important source of biologically active natural compounds that could be considered therapeutic agents. In this study, we described the identification, purification, and structure elucidation of two new naphthoquinone-based meroterpenoids, furaquinocins K and L, from Streptomyces sp. Je 1-369 strain, which was isolated from the rhizosphere soil of Juniperus excelsa (Bieb.). The main difference between furaquinocins K and L and the described furaquinocins was a modification in the polyketide naphthoquinone skeleton. In addition, the structure of furaquinocin L contained an acetylhydrazone fragment, which is quite rare for natural compounds. We also identified a furaquinocin biosynthetic gene cluster in the Je 1-369 strain, which showed similarity (60%) with the furaquinocin B biosynthetic gene cluster from Streptomyces sp. KO-3988. Furaquinocin L showed activity against Gram-positive bacteria without cytotoxic effects.